Patients with mesenchymal tumours and high Fusobacteriales prevalence have worse prognosis in colorectal cancer (CRC). Issue 8 (8th September 2021) - Salvucci, Manuela; Crawford, Nyree; Stott, Katie; Bullman, Susan; Longley, Daniel B; Prehn, Jochen H M
Abstract : Objectives: Transcriptomic-based subtyping, consensus molecular subtyping (CMS) and colorectal cancer intrinsic subtyping (CRIS) identify a patient subpopulation with mesenchymal traits (CMS4/CRIS-B) and poorer outcome. Here, we investigated the relationship between prevalence of Fusobacterium nucleatum ( Fn ) and Fusobacteriales, CMS/CRIS subtyping, cell type composition, immune infiltrates and host contexture to refine patient stratification and to identify druggable context-specific vulnerabilities. Design: We coupled cell culture experiments with characterisation of Fn / Fusobacteriales prevalence and host biology/microenviroment in tumours from two independent colorectal cancer patient cohorts (Taxonomy: n=140, colon and rectal cases of The Cancer Genome Atlas (TCGA-COAD-READ) cohort: n=605). Results: In vitro, Fn infection induced inflammation via nuclear factor kappa-light-chain-enhancer of activated B cells/tumour necrosis factor alpha in HCT116 and HT29 cancer cell lines. In patients, high Fn / Fusobacteriales were found in CMS1, microsatellite unstable () tumours, with infiltration of M1 macrophages, reduced M2 macrophages, and high interleukin (IL)-6/IL-8/IL-1β signalling. Analysis of the Taxonomy cohort suggested that Fn was prognostic for CMS4/CRIS-B patients, despite having lower Fn load than CMS1 patients. In the TCGA-COAD-READ cohort, we likewise identified a differential association between Fusobacteriales relative abundance and outcome when stratifying patients in mesenchymal (either CMS4 and/or CRIS-B) versus non-mesenchymal (neither CMS4 nor CRIS-B). Patients with mesenchymal tumours and high Fusobacteriales had approximately twofold higher risk of worse outcome. These associations were null in non-mesenchymal patients. Modelling the three-way association between Fusobacteriales prevalence, molecular subtyping and host contexture with logistic models with an interaction term disentangled the pathogen–host signalling relationship and identified aberrations (including NOTCH, CSF1-3 and IL-6/IL-8) as candidate targets. Conclusion: This study identifies CMS4/CRIS-B patients with high Fn / Fusobacteriales prevalence as a high-risk subpopulation that may benefit from therapeutics targeting mesenchymal biology.